1998
DOI: 10.1016/s1074-7613(00)80590-7
|View full text |Cite
|
Sign up to set email alerts
|

Wiskott-Aldrich Syndrome Protein-Deficient Mice Reveal a Role for WASP in T but Not B Cell Activation

Abstract: The Wiskott-Aldrich syndrome (WAS) is a human X-linked immunodeficiency resulting from mutations in a gene (WASP) encoding a cytoplasmic protein implicated in regulating the actin cytoskeleton. To elucidate WASP function, we disrupted the WASP gene in mice by gene-targeted mutation. WASP-deficient mice showed apparently normal lymphocyte development, normal serum immunoglobulin levels, and the capacity to respond to both T-dependent and T-independent type II antigens. However, these mice did have decreased per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
423
4
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(449 citation statements)
references
References 61 publications
21
423
4
1
Order By: Relevance
“…Treg cell suppression function depends on TCR stimulation (40) and requires direct cell-cell interaction (41). WASp deficiency is associated with defective TCR-mediated activation and impaired formation of the immunological synapse (6)(7)(8)(9)(42)(43)(44), both of which may affect Treg cell suppression activity. Interestingly, the partial rescue of in vitro suppression defects by pre-activation of WASp-deficient Treg cells with IL-2, suggests that optimization of T cell activation may overcome the defect of WAS Treg cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treg cell suppression function depends on TCR stimulation (40) and requires direct cell-cell interaction (41). WASp deficiency is associated with defective TCR-mediated activation and impaired formation of the immunological synapse (6)(7)(8)(9)(42)(43)(44), both of which may affect Treg cell suppression activity. Interestingly, the partial rescue of in vitro suppression defects by pre-activation of WASp-deficient Treg cells with IL-2, suggests that optimization of T cell activation may overcome the defect of WAS Treg cells.…”
Section: Discussionmentioning
confidence: 99%
“…Was -/Y and Was -/-(129S6/SvEvTac-Was tm1Sbs /J) (8) and control 129S6/SvEvTac mice were obtained from Jackson Laboratory and Taconic, respectively and maintained in sterile housing with sterile food and water. Mice were maintained and experiments performed according to NHGRI Animal Care and Use Committee guidelines.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…The biological activity of WASp in stem cell populations is witnessed by the apparent non-random distribution of X-inactivation in female carriers of a mutant WASP gene, 35 and the demonstration of homing and engraftment defects in mutant mice. 36 The widespread but hematopoietic-restricted expression profile of WASp is dictated by WASP gene regulatory elements which are therefore attractive for expression of many hematopoietic genes.…”
Section: Lentiviral Vectors Transcriptionally Targeted To Hematopoietmentioning
confidence: 99%
“…Murine models of WASP deficiency have been developed, 24,25 and recent results in our laboratory have shown that the phenotype can be corrected by stem cell transplantation. 26 Further, we have shown that WASP-deficient mice have impaired defenses against mycobacterial infection and secondary influenza challenge (Strom T, Lang R, and Turner S, unpublished observations).…”
Section: Correction Of Was Patient-derived T Cells Ts Strom Et Almentioning
confidence: 99%